Proposição de estratégias de manutenção de pavimentos aeroportuários baseadas na macrotextura e no atrito: estudo de caso do aeroporto Internacional de Fortaleza - Oliveira, Francisco Heber Lacerda de (2009)
The integral functioning of an airport complex necessarily depends on the adequate operating condition of the infrastructure related to the movement of aircraft on ground, that is, of the pavement of the runways, taxiways and the aprons. The precariousness, the inefficiency or the inexistence of these facilities, especially the runways, become the operations of aircraft impracticables and its support equipment in an airport. The gradual deterioration of these pavements is one of the factors contributing to occurrences of incidents and/or accidents involving the aircrafts. In this problem, the practices of conservation and restoration of airports pavements should be treated with priority and responsibility for their managers, although this task is very difficult and the financial resources involved, in most cases, are high and scarce. These practices point to the essential need to be included in a Airport Pavement Management System, this acts as a essential tool in managing the infrastructure and the decision-making process and are implemented on the basis of internationally recognized functional parameters, such as the macrotexture and the coefficient of friction. These relevants variables, for their obvious contributions to flight safety, are also recommended by the International Civil Aviation Organization and implemented in the main brazilian airports through regulation of the Civil Aviation National Agency. This research, therefore, aims to propose strategies for maintenance of airport pavement based on the functional parameters mentioned above and was held at Pinto Martins International Airport, in Fortaleza, state of Ceará, in view of its importance to the development of the Brasilian Northeast region, and mainly by the degradation found in their pavements, in particular its runways, caused by lack of regular practice of conservation and restoration throughout its operation. Data obtained from tests that runway show serious functional problems, with emphasis on the area corresponding to the point of touch of the aircraft.